INFANT INCUBATOR DESIGN USING ERGONOMIC FUNCTION DEPLOYMENT (EFD) METHOD TO IMPROVE COMFORT AND EFFECTIVENESS OF NEONATAL CARE - Bora, M Ansyar (J@ti Undip: Jurnal Teknik Industri, 2025)
This study aims to optimize the ergonomic design of an infant incubator using the Ergonomic Function Deployment (EFD) approach to improve the comfort and effectiveness of neonatal care in the neonatal intensive care unit (NICU). An infant incubator is an essential device that provides a stable and controlled environment for premature infants or those with medical conditions requiring intensive care. Key issues examined include infant comfort in the incubator, accessibility and ease of use for healthcare professionals, and efficiency of the control system and interface. Current incubator designs often do not fully consider these ergonomic aspects, which can negatively impact clinical outcomes and the experience of neonatal care. This study will use the EFD method to identify ergonomic needs from the perspective of the infant and healthcare professionals. The research methods used will include evaluation of current incubator designs, data collection from potential users (including infants and healthcare professionals), and analysis to identify existing ergonomic issues. The results of this study recommend technical features such as accurate digital temperature sensors, hypoallergenic materials, visual and audio alarm systems, diffusers for air ventilation, adjustable lighting, HEPA filters to maintain air quality, and ergonomic and easily accessible incubator dimension designs.